Sikap Bahasa Mahasiswa dan Implikasinya terhadap Pembelajaran Bahasa Indonesia di Perguruan Tinggi - Mansyur, Umar (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2019)
This study aimed to describe the students’ language attitudes toward Indonesian language course and its implication in higher education. This research method was a case study. The participants in this study were 92 students of Faculty of Literature at Universitas Muslim Indonesia Makassar. The data were collected by using a questionnaire technique which developed by three indicators such as loyalty attitude, pride attitude, and awareness of language norms. The data collected was analyzed statistically by using SPSS program and the results were converted into four attitude categories; very positive, positive, positive enough, and negative. The results showed that, overall, the students’ attitude toward Indonesian language was in very positive category (68% of students numbe,r). Definitely, the students’ loyalty attitude was in the very positive category (77% of students number), the pride attitude was in the very positive category (61% of students number), and students’ awareness of language norms was in a positive category (70% of students number). Furthermore, the results of this study implied to be considered to the development of teaching Indonesian language becomes more creative and innovative and the development of qualified coursebook of Indonesian Language in higher education which suitable with current development.